Foreign capital and economic growth - Eswar S. Prasad; Raghuram G. Rajan; Arvind Subramanian (Institute for the Study of Labor (IZA), 2007)
We document the recent phenomenon of uphill flows of capital from nonindustrial to industrial countries and analyze whether this pattern of capital flows has hurt growth in nonindustrial economies that export capital. Surprisingly, we find that there is a positive correlation between current account balances and growth among nonindustrial countries, implying that a reduced reliance on foreign capital is associated with higher growth. This result is weaker when we use panel data rather than cross-sectional averages over long periods of time, but in no case do we find any evidence that an increase in foreign capital inflows directly boosts growth. What explains these results, which are contrary to the predictions of conventional theoretical models? We provide some evidence that even successful developing countries have limited absorptive capacity for foreign resources, either because their financial markets are underdeveloped, or because their economies are prone to overvaluation caused by rapid capital inflows.
Keywords: F3; 330; North-South capital flows; financial globalization; Kapitalimport; Wirtschaftswachstum; Leistungsbilanz; Entwicklungsländer; Schwellenländer